SAVINGS AND LOAN INFORMATION SYSTEM, RURAL CREDIT COOPERATIVES RAHAYU REJOTANGAN WRITER DISTRICT EAST JAVA USING MICROSOFT ACCESS 2002 - Fransisca Krisnawati; Drs. Sutarno Usna, MMSI (Jurnal Sistem Informasi, 2005)
Rahayu Credit Cooperatives located in the Village District Rejotangan Credit Unions Tulungagung is aimed to meet the capital for their members and surrounding communities as farmers, mostly freshwater fish. In this information technology era of information that previously processed manually, especially in the scale of organization such as credit cooperatives will be better if all the data both member data, accounting data was done by computerized recording and storage, due to manual processing often face constraints in terms of both time and data accuracy. Then the author gives its explanation of how to design an information system from planning, analysis, design to implementation and its attachments-attachments.